Workshop report on Stakeholder Validation of Selected Adaptation Interventions in Senegal, Dakar, Senegal, 11 July 2023 - Ndione, Y. C.; Tall, L.; Sall, S.; Ciss, P. N.; Rousseau, E.; Amarnath, Giriraj; Okem, Andrew (International Water Management Institute, 2023)
Senegal, a country in West Africa and home to over 16 million people is highly vulnerable to the impacts of climate change, which interacts with existing environmental and socio-economic challenges. It is a water-scarce country. Decreasing rainfall frequent and intense droughts are exacerbating water-related impacts of climate change with vulnerable communities in rural areas bearing the highest burden of these impacts. Although agriculture is an important contributor to Senegal’s economy, it is largely rain-fed, thus increasing its vulnerability to the impacts of climate change. Against the backdrop of the increasing impacts of climate change, the CGIAR Initiative on Climate Resilience is setting up a polycentric governance model to enhance resilience against the impacts of climate change in Senegal. The study is part of a broader project titled Building Systemic Resilience Against Climate Variability and Extremes (ClimBeR). ClimBeR comprises four work modules: (1) reducing the risks associated with climate change for agricultural production systems and livelihoods; (2) strengthening the resilience of production systems by recognizing the links between climate, agriculture, security and peace; (3) Developing adaptation tools to inform policy and facilitate investment; (4) Conceptualizing a polycentric and bottom-up governance model. ClimBeR aims to strengthen climate resilience in low- and middle-income countries. This report presents the outcome of a stakeholder workshop held on 11 July 2023 as part of the project implementation. The workshop aimed to inform stakeholders about ClimBeR, share the preliminary results of the mapping exercise which culminated in an inventory of 31 promising, resilient, transformative adaptation interventions in Senegal, and select 3-4 promising, resilient and transformative adaptation interventions in Senegal from a shortlist of 8 interventions. At the end of the workshop, 4 adaptation interventions, including one recommended by the stakeholders outside the 8 preselected interventions were selected. All the selected projects operate across spatial scales with various stakeholders, including households, community members, civil society and non-governmental organisations, and government officials. Three projects focused on food security, while the fourth focused on natural resource management. The next phase of the project entails a detailed mapping of the selected interventions.